The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.exer.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular shape, conformability, net surface charge, and tissue interaction on transscleral macromolecular diffusion

Abstract: Purpose: To study the influence of molecular shape, conformability, net surface charge and tissue interaction on transscleral diffusion.Methods: Unfixed, porcine sclera was clamped in an Ussing chamber. Fluorophore labelled, neutral, albumin, dextran, or ficoll were placed in one hemi-chamber and the rate of transscleral diffusion was measured over 24 hours using a spectrophotometer. Experiments were repeated using dextrans and ficoll with positive, or negative, net surface charges.Fluorescence recovery after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Despite all these variability sources, it is remarkable the good agreement between our macroscopic diffusivity data and that obtained with FRAP and other microscopic assays. Accordingly, our work expands a recent study that used a Nanodrop spectrophotometer to assess the apparent diffusivity in scleral tissue [36], and altogether support that spectrophotometer-based assays provide a suitable and costeffective alternative to assess the apparent diffusivity in ECM gels used in 3D cultures with reasonable accuracy.…”
Section: Discussionsupporting
confidence: 81%
“…Despite all these variability sources, it is remarkable the good agreement between our macroscopic diffusivity data and that obtained with FRAP and other microscopic assays. Accordingly, our work expands a recent study that used a Nanodrop spectrophotometer to assess the apparent diffusivity in scleral tissue [36], and altogether support that spectrophotometer-based assays provide a suitable and costeffective alternative to assess the apparent diffusivity in ECM gels used in 3D cultures with reasonable accuracy.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, Wen et al compared proteins and dextrans and found that dextrans had a higher normalized permeability across the sclera (permeation coefficient normalized by the aqueous diffusion coefficient) compared with proteins of similar MW, probably because of higher structure flexibility, analogously to reports of diffusion of proteins and polysaccharides across other porous membranes. On the contrary, Srikantha et al reported slower diffusion of neutral dextran and neutral Ficoll compared with that of albumin.…”
Section: Resultsmentioning
confidence: 93%
“…The analysis of the data in Table does not permit to draw conclusions of the effect of the charge on the permeability of macromolecules, also because differences in the charge often follow differences in the shape and conformation. In this regard, Srikantha et al studied macromolecules diffusion across the sclera using neutral, cationic and anionic Ficoll and dextrans with MW of 70 kDa. Their results indicate that a charge have a different impact on the permeability, depending on the structure of the molecules, suggesting that a charge can have an indirect effect because of a change in the molecular conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Drug injected into SC space has direct access into intraocular tissue through transscleral route and fast clearance via conjunctival blood and lymphatic flow Urtti 2006, Amrite et al 2008). Larger accessible surface area of sclera and a high degree of hydration make it permeable to hydrophilic substances (Srikantha et al 2012). Scleral matrix is having proteoglycans which contributes to negative charge on the sclera and may bind to positively charged molecules (Ranta et al 2010).…”
Section: Introductionmentioning
confidence: 99%